LAND AND ITS RELATIONSHIP TO POSTCOLONIAL PERSPECTIVES IN AMA ATTA AIDO’S PLAY “ANOWA” AND ARUNDHATI ROY’S NOVEL “THE GOD OF SMALL THINGS” - Ameen, Hishryar M. (Humanities Journal of University of Zakho, 2017)
This paper discusses the issue of land within the postcolonial perspective. Land has always been a shelter protecting nations from disappearing. In this context, land for the postcolonial people does not only represent a specific area in the globe, but more as a sign of their identity and recognition. The placement and displacement of people from their land means much more than simply leaving to another zone, but it refers to the whole element of identity, culture, language, and existence. This research studies two literary works written by writers from colonialized nations. It aims at exploring the theme of land and the identity by two writers from two different nations; from India and Ghana. The text “The God of Small Things” was written by an Indian writer named Arundhati Roy, while the other text is “Anowa” written by Ama Atta Aidoo. The concept of land was pictured in the works of these two writers as the source of being and existence of the nations. This paper discusses the issue of land within the postcolonial perspective. Land has always been a shelter protecting nations from disappearing. In this context, land for the postcolonial people does not only represent a specific area in the globe, but more as a sign of their identity and recognition. The placement and displacement of people from their land means much more than simply leaving to another zone, but it refers to the whole element of identity, culture, language, and existence. This research studies two literary works written by writers from colonialized nations. It aims at exploring the theme of land and the identity by two writers from two different nations; from India and Ghana. The text “The God of Small Things” was written by an Indian writer named Arundhati Roy, while the other text is “Anowa” written by Ama Atta Aidoo. The concept of land was pictured in the works of these two writers as the source of being and existence of the nations. This paper is divided into several sub topics. First, it gives an introduction. Then it discusses land in the perspective of postcolonial literature. Next, it explains the objectives behind the opening sentences of the two texts. Following this part, the paper shows the importance of land being the identity of nations. Subsequently, land has become the source of being and life. Consequently, it propose homeland as the best place for living of a nation and the importance of one sticking to their home and serving it. Finally, it comes to a conclusion that people should raise their national spirit towards their place of origin and serve it in order to avoid future colonialism campaigns and prevent the consequences.